Doing academic careers differently : portraits of academic life - Robinson, Sarah, 1964-; Bristow, Alexandra, 1979-; Ratle, Olivier, 1975- (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"Should academic careers always unfold in exactly the same way? Is there one best way of being an academic? This book says no. Assumptions about who academics are and what they should do are becoming increasingly narrow and focused on achieving so-called 'excellence' in teaching and research above anything else. This book problematises this and explores the scope for doing academic careers differently. Authors paint individual or group portraits of their academic careers, working with metaphors which challenge the dominant discourses of how academic careers should be led. From rejecting the pressure to focus on 'one big thing', to prioritising nurture and care, transcending disciplinary boundaries, reshaping own daily practice, connecting with communities, and being academics outside academia, the chapters in this book offer those considering, starting or developing an academic career a treasure trove of many alternative possibilities. Presented as a portrait gallery through which readers are encouraged to meander at will, this compilation of insights into alternative academic lives will help to inspire and encourage current academics to re-think and take ownership of their careers in their own terms, according to their own strengths, weaknesses and circumstances"--
Keywords: College teachers; Career development; BUSINESS & ECONOMICS / Careers / General